Functional interaction between neuropeptide Y receptors and modulation of calcium channels in the rat hippocampus - Silva, Ana P. (2003)
We investigated the functional interaction between neuropeptide Y (NPY) receptors using nerve terminals and cultured rat hippocampal neurons, and we evaluated the involvement of voltage-gated Ca2+ channels (VGCCs) in NPY receptors-induced inhibition of Ca2+ influx and glutamate release. The KCl-evoked release of glutamate from hippocampal synaptosomes was inhibited by 1 [mu]M NPY and this effect was insensitive to either BIBP3226 (Y1 receptor antagonist) or L-152,804 (Y5 receptor antagonist), but was sensitive to BIIE0246 (Y2 receptor antagonist). We could also pharmacologically dissect the NPY receptors activity by using Y1, Y2 and Y5 receptor agonists ([Leu31,Pro34]NPY, NPY13-36, NPY (19-23)-(Gly1,Ser3,Gln4,Thr6,Ala31,Aib32,Gln34)-pancreatic polypeptide (PP), respectively), and in all the cases we observed that these agonists could inhibited the KCl-induced release of glutamate. However, the selective and specific co-activation of both Y1 and Y2 or Y2 and Y5 receptors resulted in non-additive inhibition, and this effect was prevented in the presence of the Y2 antagonist, but was insensitive to the Y1 or Y5 receptor antagonist. Moreover, as we previously showed for Y1 receptors, we also observed that the activation of Y5 receptors inhibited the glutamate release in the dentate gyrus and CA3 subregion, without significant effect in the CA1 subregion of the hippocampus. The same qualitative results were obtained when we investigated the role of NPY Y1 and Y2 receptors in modulating the changes in [Ca2+]i due to KCl depolarisation in cultured hippocampal neurons. The inhibitory effect of nitrendipine (L-type VGCC blocker) or [omega]-conotoxin GVIA ([omega]-CgTx; N-type VGCC blocker) was not potentiated by the simultaneous activation of Y1 or Y2 receptors. Moreover, the exocytotic release of glutamate was inhibited by [omega]-agatoxin IVA ([omega]-Aga; P-/Q-type VGCC blocker), and this VGCC blocker did not potentiate Y1, Y2 or Y5 receptor-mediated inhibition of glutamate release. Also, the effect of ionomycin in inducing the exocytotic release of glutamate from hippocampal synaptosomes was insensitive to the activation of NPY receptors. In the present paper, we identified a role for NPY Y1, Y2 and Y5 receptors in modulating the exocytotic release of glutamate and the [Ca2+]i changes in the rat hippocampus. In conditions of co-activation, there appears to exist a physiological cross-talk between Y1 and Y2 and also between Y2 and Y5 receptors, in which Y2 receptors play a predominant role. Moreover, we also show that Y1 and Y2 receptors exert their inhibitory action by directly modulating L-, N-, and P-/Q-type VGCCs, whereas the inhibition of glutamate release mediated by the Y5 receptors seems to involve P-/Q-type VGCCs.